(untitled) (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To evaluate the treatment outcome in AO type C, distal femoral fractures using longer lever arm anatomical plates with minimally invasive plate osteosynthesis (MIPO) technique. Methods: This prospective cases series was done using probability sampling technique at two centers including Orthopedics and Spine Institute, Doctors Hospital, Medical Center, Lahore and Department of Orthopedics Surgery and Traumatology, Post-graduate Medical Institute, Lahore General Hospital, Lahore from January 2016 to August 2017. AO type C close distal femoral fractures fulfilling the inclusion criteria were included in the study. We fixed all fractures with longer lever arm anatomical plates with minimally invasive plate osteosynthesis (MIPO) technique. On each follow up patients were assessed using American Knee Society Score(AKSS) for functional outcome and x rays for union. SPSS version 20.00 was used to analyze the data and p-value <0.05 was taken as significant. Results: Out of the total 35 cases there were 21 (60%) males and 14 (40%) females. The mean age of the patients was 39.7429±12.577. There was primary union in 31 (88.6%) cases and non-union in two (5.8%) cases, delayed union in two (5.8%) patients. Amongst 35 cases, 32 (91.4%) didn’t required bone graft and only 03 (8.6%) had primary bone grafting due to severe comminution. Post-operatively American knee society score was excellent in 24 (68.4%), good in 6 (16.1%), fair in 04 (11.4%) and poor in only 01 (2.9%) patient. Conclusion: Longer lever arm plates with MIPO has good to excellent results regarding union, knee range of motion and minimal infection.